Capture and biological release of circulating tumor cells in pancreatic cancer based on peptide-functionalized silicon nanowire substrate - Shen Q (Dove Medical Press, 2018)
Qinglin Shen,1,2,* Haitao Yang,3,* Caixia Peng,4,5,* Han Zhu,6 Jia Mei,1 Shan Huang,1 Bin Chen,7 Jue Liu,8 Wenbo Wu,3 Shaokui Cao3 1Department of Oncology, The Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China; 2Cancer Center, Renmin Hospital, Wuhan University, Wuhan, China; 3School of Materials Science and Engineering, Zhengzhou University, Zhengzhou, China; 4Key Laboratory for Molecular Diagnosis of Hubei Province, The Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China; 5Central Laboratory, The Central Hospital of Wuhanper, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China; 6Key Laboratory of Synthetic and Biological Colloids, Ministry of Education, School of Chemical and Material Engineering, Jiangnan University, Wuxi, China; 7Central Laboratory, Renmin Hospital, Wuhan University, Wuhan, China; 8Department of Pharmacy, The Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China *These authors contributed equally to this work Background: Efficient and precise circulating tumor cells’ (CTCs) capture and release with minimal effect on cell viability for CTCs’ analysis are general requirements of CTCs’ detection device in clinical application. However, these two essential factors are difficult to be achieved simultaneously. Methods: In order to reach the aforementioned goal, we integrated multiple strategies and technologies of staggered herringbone structure, nanowires’ substrate, peptides, enzymatic release, specific cell staining, and gene sequencing into microfluidic device and the sandwich structure peptide-silicon nanowires’ substrate was termed as Pe-SiNWS. Results: The Pe-SiNWS demonstrated excellent capture efficiency (95.6%) and high release efficiency (92.6%). The good purity (28.5%) and cell viability (93.5%) of CTCs could be obtained through specific capture and biological release by using Pe-SiNWS. The good purity of CTCs facilitated precise and quick biological analysis, and five types of KRAS mutation were detected in 16 pancreatic cancer patients but not in healthy donors. Conclusion: The results proved that the effective capture, minor damage release, and precise analysis of CTCs could be realized simultaneously by our novel strategy. The successful clinical application indicated that our work was anticipated to open up new opportunities for the design of CTC microfluidic device. Keywords: circulating tumor cells, Pe-SiNWS, biological release, pancreatic cancers